2005
DOI: 10.1177/155005940503600107
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency EEG Activity during Sleep: Characteristics in Schizophrenia and Depression

Abstract: Previous studies indicate that high frequency power (>20Hz) in the electroencephalogram (EEG) are associated with feature binding and attention. It has been hypothesized that hallucinations and perceptual abnormalities might be linked to irregularities in fast frequency activity. This study examines the power and distribution of high frequency activity (HFA) during sleep in healthy control subjects and unmedicated patients with schizophrenia and depression. This is a post-hoc analysis of an archival database c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 59 publications
2
39
2
4
Order By: Relevance
“…These data add to the growing consensus that disturbed neural coordination at gamma (and beta) frequencies may underlie disorganized processing in different sensory modalities (Kwon et al, 1999;Spencer et al, 2003) during sleep and rest (Tekell et al, 2005). This predicts that the TTX-altered coactivity would occur at gamma frequencies if it reflects a schizophrenia-related phenomenon.…”
Section: Ttx-induced Cognitive Disorganizationsupporting
confidence: 54%
See 1 more Smart Citation
“…These data add to the growing consensus that disturbed neural coordination at gamma (and beta) frequencies may underlie disorganized processing in different sensory modalities (Kwon et al, 1999;Spencer et al, 2003) during sleep and rest (Tekell et al, 2005). This predicts that the TTX-altered coactivity would occur at gamma frequencies if it reflects a schizophrenia-related phenomenon.…”
Section: Ttx-induced Cognitive Disorganizationsupporting
confidence: 54%
“…Furthermore, if the TTX-induced coactivity is related to the cognitive disorganization associated with disorganization in schizophrenia, one also expects the coactivity to manifest at the timescale of gamma because altered gamma is associated with schizophrenia (Kwon et al, 1999;Spencer et al, 2003) and correlates with disorganization symptoms (Spencer et al, 2004;Tekell et al, 2005).…”
Section: Timescale Of the Ttx-induced Coactivitymentioning
confidence: 99%
“…The gamma activity in most of the case was higher in depressed subjects but has showed no significant differences in this study. These findings are in agreement with results of [15,19] which reported increase of beta and gamma activity in depressed subjects.…”
Section: Discussionsupporting
confidence: 94%
“…They also shown that the power density in the entire frequency range (0.25 to 25 Hz) exhibited a decreasing trend over the first three NREM/REM sleep cycles for both groups, but in each cycle depressed people had lower values than controls [6], although this result was breached in later years by Mendelson et al [7]. Tekell and colleagues in their work demonstrated increase of high frequencies activity in these patients [15]. It was shown that high frequencies and beta are greater in depressed women compared with depressed men, especially in right hemisphere [16].…”
Section: Introductionmentioning
confidence: 89%
“…Finally, lower levels of beta oscillatory activity have been observed in patients with schizophrenia (Rutter et al, 2009). In sleep studies, unmedicated patients had higher beta power at all stages of the sleep compared to healthy individuals (Tekell et al, 2005). Alternatively, deficient power and synchronization of evoked and induced EEG rhythms in the beta and gamma bands have frequently been reported (Clementz et al, 1997, Cho et al, 2006, Uhlhaas et al, 2006.…”
Section: Event-related Spectral Perturbations (Ersp) Abnormalities Inmentioning
confidence: 99%